Infant Infections and Respiratory Symptoms in Relation to in Utero Arsenic Exposure in a U.S. Cohort - Farzan, Shohreh F. (Environ Health Perspect, 2015)
BACKGROUND: Arsenic has been linked to disrupted immune function and greater infection susceptibility in highly exposed populations. Well arsenic levels above the U.S. EPA limit occur in our U.S. study area and are of particular concern for pregnant women and infants. OBJECTIVES: We investigated whether in utero arsenic exposure affects the risk of infections and respiratory symptoms over the first year of life. METHODS: We prospectively obtained information on infant infections and symptoms, including their duration and treatment (n = 412) at 4, 8, and 12 months using a parental telephone survey. Using generalized estimating equation models adjusted for potential confounders, we evaluated the association between maternal pregnancy urinary arsenic and infant infections and symptoms over the first year. RESULTS: Each doubling of maternal urinary arsenic was related to increases in the total number of infections requiring prescription medication in the first year [relative risk (RR) = 1.1; 95% CI: 1.0, 1.2]. Urinary arsenic was related specifically to respiratory symptoms (difficulty breathing, wheezing, and cough) lasting ≥ 2 days or requiring prescription medication (RR = 1.1; 95% CI: 1.0, 1.2; and RR = 1.2; 95% CI: 1.0, 1.5, respectively), and wheezing lasting ≥ 2 days, resulting in a doctor visit or prescription medication treatment (RR = 1.3; 95% CI: 1.0, 1.7; RR = 1.3; 95% CI: 1.0, 1.8, and RR = 1.5; 95% CI: 1.0, 2.2, respectively). Associations also were observed with diarrhea (RR = 1.4; 95% CI: 1.1, 1.9) and fever resulting in a doctor visit (RR = 1.2; 95% CI: 1.0, 1.5). CONCLUSIONS: In utero arsenic exposure was associated with a higher risk of infection during the first year of life in our study population, particularly infections requiring medical treatment, and with diarrhea and respiratory symptoms. CITATION: Farzan SF, Li Z, Korrick SA, Spiegelman D, Enelow R, Nadeau K, Baker E, Karagas MR. 2016. Infant infections and respiratory symptoms in relation to in utero arsenic exposure in a U.S. cohort. Environ Health Perspect 124:840–847; http://dx.doi.org/10.1289/ehp.1409282